Evaluation of flammable volume in the case of a catastrophic leak of R-32 from a rooftop unit. (July 2018) - Elatar, Ahmed; Abu-Heiba, Ahmad; Patel, Viral; Edwards, K Dean; Baxter, Van; Abdelaziz, Omar; Zhang, Mingkan
Highlights: The leaked refrigerant mass flow rate affects its distribution inside the duct. Catastrophic leak of R-32 from 3-ton package unit caused a maximum flammable volume of 0.11% of the room size. The flammable volume is confined to the space below the outlet where the leaked refrigerant is entering the room from. Abstract: With the effort to use alternative refrigerants with lower global warming potential (GWP), the majority of these alternative refrigerants are classified as slightly flammable. In this paper we report on the numerical evaluation of a catastrophic leak scenario of R-32 refrigerant from a 3-ton roof top air conditioning unit (RTU) which serves a 12.2 × 9.14 × 2.4 m room. A full rupture of a 6.35 mm (¼ inch) pipe downstream of the evaporator coil is simulated. Two separate cases with refrigerant releases of 1.81 kg and 3.62 kg charge have been studied. The two charges are released in 10.2 and 20.4 s, respectively, just after the end of a unit cooling cycle. The flammable volume inside the room existed only for about 40 s with a maximum flammable volume inside the room of 1.12% of the total room volume for the 3.62 kg charge case.